Influence of hybrid nanofluids on entropy dynamics and transient thermal behavior in a finned enclosure with cylindrical obstruction - Chunyang Li; Hassan Roshani; Mohammad Jalili; Mohamed H. Mohamed; Payam Jalili; Bahram Jalili; Irshad Ahmad; Qasem M. Al-Mdallal (Case Studies in Thermal Engineering)
The purpose of this research was to the flow behavior, heat transfer rate, and entropy generation by the hybrid nanofluid flow (Al2O3+Cu + H2O) inside a square finned cavity containing a cylindrical barrier in its upper half in a time interval of 20 seconds. Al2O3 and Cu nanoparticles have concentrations of 5 % and 3 %, respectively, and water is chosen as the base fluid. In this research, Reynolds and Richardson numbers represent inertial and buoyant forces. In the square cavity geometry, two fins with a length of 0.3 and a width of 0.1 are embedded in the vertical walls, and the four corners of the cavity have 90° sectors. The entropy generation is also investigated using the derived profiles, and the heat transfer rate is computed using the average and local Nusselt numbers. The hybrid nanofluid flow's governing equations were resolved by applying the Galerkin finite element method. The findings showed that as the Richardson number in each of the Reynolds numbers rose, so did the hybrid nanofluid's horizontal and vertical velocities during the designated period and that the temperature distribution from the lower surface to the top half of the cavity expanded.